Palladium-catalyzed synthesis of spirooxindoles and [3, 4]-fused oxindoles from alkene-tethered carbamoyl chlorides. Issue 2 (27th November 2020) - Yang, Fang; Sun, Wan; Meng, Haifang; Chen, Mengjia; Chen, Chen; Zhu, Bolin
Abstract : We disclosed an efficient Pd-catalyzed domino reaction for the synthesis of spirooxindoles and [3, 4]-fused oxindoles from alkene-tethered carbamoyl chlorides. Abstract : We disclosed an efficient Pd-catalyzed domino reaction for facile synthesis of spirooxindoles and [3, 4]-fused oxindoles from alkene-tethered carbamoyl chlorides. The five-membered C, C -palladacycle obtained through intramolecular C–H activation should act as the key intermediate in both catalytic cycles. A variety of functionalized spirooxindoles and [3, 4]-fused oxindoles were synthesized in moderate to good yields.